A linear spin-wave theory for LiNiPO4 utilizing a nonextensive distribution - R. Navarro, F. A. (2012)
This work is concerned about the lithium-nickel phosphate, LiNiPO4, a very important magneticelectric material due to its promising applications to tailor the next-generation lithium-nickel batteries. In the Hamiltonian operator, it is considered the interactions of Ni2+, the unique magnetic ion in the phosphate. Specifically, it is taken into account the Heisenberg interactions along with the single-ion anisotropy term. Furthermore, the utilization of the Holstein-Primakoff formalism leads to spin-wave scattering. To investigate the spin-wave intensities, we utilize the nonextensive probability distribution what originates some bulges in the curves of the intensities.